The Relationship Between Surgical Patients and Nurses Characteristics With Their Perceptions of Caring Behaviors: A European Survey. (April 2014) - Patiraki, Elisabeth; Karlou, Chryssoula; Efstathiou, Georgios; Tsangari, Haritini; Merkouris, Anastasios; Jarosova, Darja; Leino-Kilpi, Helena; Suhonen, Riitta; Balogh, Zoltan; Palese, Alvisa; Tomietto, Marco; Papastavrou, Evridiki
The purpose of this European survey was to examine the relationship of surgical patients' and nurses' personal characteristics with their perceptions of caring behaviors. Caring Behaviors Inventory (CBI) was completed by convenience samples of 1, 659 patients and 1, 195 nurses from six countries of Europe. The results showed that the older the patients, the more positive were their evaluations of CBI. Those with planned admission and good/very good health conditions gave higher ratings compared to those with an emergency and poor health conditions. Type of admission, age, and health conditions explained 5.2% of CBI variance. Nurses with more work experience and experience in the unit gave significantly higher ratings compared to nurses with less experience. Nurses' total experience and gender explained 2.3% of the variance of perceived care. Therefore, in a multinational surgical environment, caring behaviors may be influenced by other variables, better captured by using different research methods.